Challenging factors of farmer-to-consumer direct marketing: An empirical analysis of German livestock owners - Stefan Clemens Wille; Britta Barklage; Achim Spiller; Marie von Meyer-Höfer (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2018)
Farmer-to-consumer direct marketing provides an alternative marketing strategy for farmers, ensuring their income while also meeting consumers' increasing demand for local food. This study evaluates the challenging factors of this marketing channel from the farmers' viewpoint. A CAPI survey was carried out among 121 German livestock owners. The results of a cluster analysis demonstrate that the location of the farm represents the most challenging requirement for the interviewed farmers. The cluster analysis additionally reveals that most of the livestock owners see problems with the implementation of requirements concerning the personal challenges of direct farm marketing (especially hygiene regulations, self-motivation and customer contact).
Keywords: 330; farmer-to-consumer direct marketing; local farm products; German livestock owners